2021
DOI: 10.3855/jidc.13603
|View full text |Cite
|
Sign up to set email alerts
|

Rate and predictors of HIV virological failure among adults on first-line antiretroviral treatment in Dar Es Salaam, Tanzania

Abstract: Introduction: Monitoring resistance to first line Antiretroviral therapy (ART) is crucial in preventing accumulation of viral mutations following the implementation of the World Health Organization “treat all” initiative. We estimated the rate and predictors of virological treatment failure among adults living with HIV/AIDS in Dar es Salaam, Tanzania. Methodology: A retrospective cohort study involving adults aged 18 and above receiving first line ART in Dar as Salaam between 2016 and 2018 were recruited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 33 publications
3
7
1
Order By: Relevance
“…Accordingly, male HIV patients were more likely to develop virological failure as compared to females. This study is in line with the research studies conducted in Kumasi, Ghana [ 26 ], Morocco [ 79 ], Dar Es Salaam, Tanzania [ 36 ], and the Tigray region, Ethiopia [ 80 ] that stated that virological failure was more common in male HIV patients than female HIV patients. The possible reasons might be excessive alcohol consumption, low clinic attendance for ART, and low health-seeking behavior in male patients [ 31 , 36 , 80 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Accordingly, male HIV patients were more likely to develop virological failure as compared to females. This study is in line with the research studies conducted in Kumasi, Ghana [ 26 ], Morocco [ 79 ], Dar Es Salaam, Tanzania [ 36 ], and the Tigray region, Ethiopia [ 80 ] that stated that virological failure was more common in male HIV patients than female HIV patients. The possible reasons might be excessive alcohol consumption, low clinic attendance for ART, and low health-seeking behavior in male patients [ 31 , 36 , 80 ].…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, in Ethiopia, studies reported that virologic failure rates ranged from 5.4 to 19% [ 30 32 ]. Several studies have found that socio-demographic predictors (age, gender, marital status, religion), clinical-related predictors (low BMI, TB co-infection), and treatment-related predictors (excessive dose frequency, poor medication adherence) can all influence virological failure in HIV patients [ 30 , 33 36 ]. However, the predictors of virological failure varied between studies.…”
Section: Introductionmentioning
confidence: 99%
“…20 Similarly, this result is comparable with study conducted at Dar Es salaam Tanzania, which revealed HIV positive on rst line ART, Clients who have history of TB co-infection had odds of 2.1 to develop virologic failure compared to clients with no history of TB co-infection. 27 This may be due to the fact that, like HIV, TB infection also attacks white blood cells which lead to synergistic effect with HIV to minimize CD4 count and facilitate for HIV replication which leads to HIV virologic failure.…”
Section: Discussionmentioning
confidence: 99%
“…Drugs with multiple sites of activity are essentially ‘combination therapies’ and therefore may be expected to show a high threshold for viruses to develop resistance. For example, although the rate of resistant mutation is unknown with SARS-CoV-2, it is estimated as 1 in 10 6 for HIV-1 virus 2426 . This suggests that a three-drug combination with different sites of action will acquire 1 in 10 18 resistant viruses: a number much higher than the possible viral loads in the body.…”
Section: Methodsmentioning
confidence: 99%